Le droit public après les bombes Projets de réformes constitutionnelles et législatives pour une Syrie démocratique - Kodmani, Ahmad (Droit et criminologie, 2023)
At a time when bombs are raining down on Ukraine, they have fallen silent on Syria. But another danger lurks in the latter: that of silence. To break this silence, this book discusses Syrian public law in a critical way.